A Digital Storybook with Interactive Quizzes to Improve Elementary School Students' Understanding of Sexual Education - Gita Septinauli Sidabutar; I Made Citra Wibawa; Ida Bagus Putu Arnyana (Journal of Education Reseach and Evaluation, 2026)
Elementary school students have a low understanding of the concept of protecting themselves from violence or sexual harassment, even though some students are familiar with body organs and how to maintain their hygiene. One of the causes is the lack of learning media for sexual education that is appropriate to the characteristics of lower-grade students. Based on this, the purpose of this study is to develop a Digital Storybook Assisted by Interactive Quizzes to Improve Understanding of Sexual Education in Second-Grade Elementary School Students. This type of research is development research using the ADDIE model. The feasibility of the product created was tested by 2 content experts and 2 learning media experts. 10 and 25 students conducted the practical test. The subjects of this effectiveness test were 30 people. The methods used to collect data included questionnaires and objective test methods. The instruments used to collect data were questionnaires and multiple-choice questions. The analysis methods used in this study were qualitative and quantitative. The results of the study validated the digital storybook by media experts (average score of 96.5%) and material experts (96.25%; very valid). The teacher's assessment was 4.78, and the student's was 4.76 (very practical). The effectiveness test showed a difference in average learning outcomes between the control and experimental groups after controlling for initial abilities. It was concluded that the use of digital storybooks with interactive quizzes significantly improved elementary school students' understanding of sexual education.